Effects of Mouthguards on Skin Damage In Vitro Study - Saito, Maho; Nakajima, Kazunori; Tsutsui, Arata; Sakaue, Takahiro; Kanemitsu, Anna; Takeda, Tomotaka; Fukuda, Kenichi (European Journal of Dentistry, 2022)
Objective Mouthguards can prevent and reduce orofacial sports traumas, which occur to the players themselves. However, the effect of mouthguards on skin damage has not been clarified. The present study's purpose was to examine whether the mouthguard can reduce or prevent skin damage caused by teeth (including the difference in mouthguard thickness).Materials and Methods Pigskins, artificial teeth, and Ethylene-vinyl acetate (EVA) mouthguard blanks with 1.5- and 3.0-mm thickness were employed. Each of the two type mouthguards was produced in 10 replicates. Mouthguard incisal thickness and collision touch angle were measured on a PC using imaging software. A pendulum-type machine was used to apply impact. Strain gauges attached to the tooth and impacted plate were used to measure mouthguards' effect on impact stress. Also, a microscope was used to observe the after impacted skin condition, and the extent of damage was assessed as a score.Results The pigskin was ruptured in without mouthguard (NOMG) with presenting the highest damage score, whereas the complete rupture was not seen in the 1.5 mm MG, but the damage of the skin (defeat) was observed. No tissue change was found with the 3 mmMG. In both the flat plate and impact tooth strain, no significant difference was observed between NOMG and 1.5 mmMG. However, 3 mmMG had a significantly smaller value than the other two conditions. These results are likely to be strongly influenced by the mouthguard incisal thicknesses and collision touch angles differences.Conclusion The present study results clarified that two different thickness mouthguards reduced the skin damage, and the thicker mouthguard showed more effectiveness. Therefore, mouthguards may prevent the wearer's stomatognathic system's trauma and avoid damage to the skin of other athletes they are playing with. This effect seems to be an essential basis for explaining the necessity of using mouthguards for others besides full-contact sports.
Keywords: mouthguard; prevention; skin; thickness; trauma